Text-image Iconicity in Assurnasirpal II’s Northwest Palace - Robin Baker (Studies in Ancient Art and Civilization)
Among the most celebrated archaeological discoveries and the most debated expressions of Assyrian art is the bas-relief that stood behind the throne in Assurnasirpal II’s Northwest Palace in Nimrud. Most attempts to interpret the panel have focused on specific elements of its iconography, particularly the tree and the figure in the winged disk above it. Many scholars have sought to decipher the image by comparing it with series of panels from elsewhere in the palace. Some studies have also explored the relief’s relationship to its inscription. Despite the extensive literature on the artifact, its meaning has remained elusive. This study approaches the conundrum from a different angle. It considers the relief’s text-image iconicity through the lens of Assurnasirpal’s theology, since both express theological conceptions. It investigates the theological relationship between the image and the placement of the cuneiform signs carved on it, thereby shedding light on the meaning of the imagery.